Glycosaminoglycans in extracellular matrix organisation: are concepts from soft matter physics key to understanding the formation of perineuronal nets? - Richter, Ralf P; Baranova, Natalia S; Day, Anthony J; Kwok, Jessica Cf (Current opinion in structural biology, 2018)
Conventional wisdom has it that proteins fold and assemble into definite structures, and that this defines their function. Glycosaminoglycans (GAGs) are different. In most cases the structures they form have a low degree of order, even when interacting with proteins. Here, we discuss how physical features common to all GAGs-hydrophilicity, charge, linearity and semi-flexibility-underpin the overall properties of GAG-rich matrices. By integrating soft matter physics concepts (e.g. polymer brushes and phase separation) with our molecular understanding of GAG-protein interactions, we can better comprehend how GAG-rich matrices assemble, what their properties are, and how they function. Taking perineuronal nets (PNNs)-a GAG-rich matrix enveloping neurons-as a relevant example, we propose that microphase separation determines the holey PNN anatomy that is pivotal to PNN functions.
Keywords: Protein Binding; Extracellular Matrix Proteins; Neurons; Glycosaminoglycans; glykosaminoglykany; extracelulární matrix - proteiny; extracelulární matrix; Hydrophobic and Hydrophilic Interactions; neurony; hydrofobní a hydrofilní interakce; Extracellular Matrix; vazba proteinů